Opportunities for the development of a borderland rural territory: A case study of the Hlučín region - Šťastná, Milada; Vaishar, Antonín (Quaestiones Geographicae, 2023)
The study evaluates the regional development potential of a specific rural micro-region with regard to its qualitative aspect. It aims to set a general strategy for further development. The method is a geographical analysis using the migration balance as an indicator of the region’s attractiveness for housing. Main strengths, weaknesses, opportunities and threats were identified. Generally accessible statistical data was used. The proposed strategy is to support the development of the human capital. In addition to the generally valid recommendations for the development of rural areas, it is always necessary to take into account the peculiarities of the geographical location, path dependency, natural, economic and social potential, the state of the environment, cultural factors or other specifics. The regional and local decision-making levels play an important role in this process.